Ergativity and other alignment types in neo-Aramaic: investigating morphosyntactic microvariation - Noorlander, Paul M. (Studies in Semitic languages and linguistics, 2021)
The alignment splits in the Neo-Aramaic languages display a considerable degree of diversity, especially in terms of agreement. While earlier studies have generally oversimplified the actual state of affairs, Paul M. Noorlander offers a meticulous and clear account of nearly all microvariation documented so far, addressing all relevant morphosyntactic phenomena. By means of fully glossed and translated examples, the author shows that this vast variation in morphological alignment, including ergativity, is unexpected from a functional typological perspective. He argues the alignment splits are rather the outcome of several construction-specific processes such as internal system harmonization and grammaticalization, as well as language contact.. Readership: All interested in linguistics, especially language typology, syntax and morphology, and contact between languages of the Middle East, particularly Aramaic-Iranian. Examples are fully glossed and translated